Pengaruh Reputasi dan Produk Bank terhadap Keputusan Menabung pada PT Bank Muamalat Indonesia KC Payakumbuh - Safitri, Hafizah; Kenedi, Jon (Lembaga Yasin AlSys, 2024)
The credibility and bank products of PT Bank Muamalat Indonesia KC Payakumbuh on saving decisions are the driving forces behind this study. This study aims to ascertain how bank reputation and offerings at Bank Muamalat Payakumbuh influence consumers' decisions to save. Using a descriptive methodology and quantitative research approaches, this study examines 3,754 customers with a sample size of 100 respondents. The methods of collecting data are questionnaires and observation. This study includes one dependent variable, saving decisions, and two independent variables, bank reputation, and products. A simultaneous test (F test) and an individual significant test (T-test) are two types of data analysis used to test the hypothesis.